Dual role of TLR4 in bacterial meningitis through regulating endothelial pyroptosis and inflammatory response during extraintestinal pathogenic Escherichia coli infection - Kaixiang Jia; Yangyang Du; Weixian Lin; Xuefeng Cao; Xuefeng Cao; Jialu Zhang; Jialu Zhang; Lianci Peng; Lianci Peng; Zhiwei Li; Zhiwei Li; Rendong Fang; et al. (Frontiers in Immunology)
Bacterial meningitis is a severe central nervous system infection with incompletely understood pathogenesis. Here, we investigated the role of Toll-like receptor 4 (TLR4) in blood-brain barrier disruption induced by extraintestinal pathogenic Escherichia coli (ExPEC). In vitro studies revealed that ExPEC infection upregulated TLR4 expression in human brain microvascular endothelial cells and induced pyroptosis and tight junction protein degradation. TLR4 inhibition by TAK-242 significantly reduced pyroptosis and inflammatory responses but exacerbated tight junction disruption and bacterial invasion. In macrophages, TLR4 inhibition similarly attenuated pyroptosis and inflammatory responses. Interestingly, despite enhanced blood-brain barrier disruption and increased bacterial burden, TLR4-deficient mice showed significantly improved survival. Transcriptome analysis revealed that TLR4 deficiency triggered comprehensive reprogramming of host responses, characterized by both suppressed inflammatory damage and enhanced tissue homeostatic processes. This study demonstrates for the first time that endothelial pyroptosis is a novel mechanism for ExPEC-induced blood-brain barrier disruption and reveals the crucial role of TLR4 in balancing protective and destructive host responses, providing new insights for therapeutic strategies against bacterial meningitis.